2012
DOI: 10.1007/s13197-012-0890-x
|View full text |Cite
|
Sign up to set email alerts
|

Yoghurt with candied chestnut: freeze drying, physical, and rheological behaviour

Abstract: As a novel product, yoghurt powder was produced by freeze drying and with added candied chestnut puree at ratios of 5, 10, and 20 % by weight. During the freeze drying process, mass loss, water activity, and the moisture content of the samples were determined and the colour (Hunter L, a, b) of the yoghurt powder products was measured. Results showed that increasing the percentage of candied chestnut puree resulted in an increase in water activity, moisture content, and colour change values of the end product. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Consumers are now becoming even more discerning and demands products with improved sensory attributes, enriched with nutrients and manufactured from natural components with simple and clear labels. This leads to development of different types of dahi (Indian yoghurt) and yoghurts such as dietary fiber (soy, oat and inulin) enriched yoghurt (Raju and Pal 2014); low-fat set-type yoghurt (Pakseresht et al 2017); flaxseed oil and flour incorporated fruit yoghurt (Kumar et al 2017); low phenylalanine yoghurt (Goldar et al 2016); Bambara groundnut (Vigna subterranea) and soybeans (Glycine max) based yoghurt (Falade et al 2015); yoghurt containing candied chestnut (Sakin-Yilmazer et al 2014); omega-3 fatty acids fortified Indian yoghurt (Goyal et al 2016); bglucan fortified dahi (Bhaskar et al 2017) etc.…”
Section: Introductionmentioning
confidence: 99%
“…Consumers are now becoming even more discerning and demands products with improved sensory attributes, enriched with nutrients and manufactured from natural components with simple and clear labels. This leads to development of different types of dahi (Indian yoghurt) and yoghurts such as dietary fiber (soy, oat and inulin) enriched yoghurt (Raju and Pal 2014); low-fat set-type yoghurt (Pakseresht et al 2017); flaxseed oil and flour incorporated fruit yoghurt (Kumar et al 2017); low phenylalanine yoghurt (Goldar et al 2016); Bambara groundnut (Vigna subterranea) and soybeans (Glycine max) based yoghurt (Falade et al 2015); yoghurt containing candied chestnut (Sakin-Yilmazer et al 2014); omega-3 fatty acids fortified Indian yoghurt (Goyal et al 2016); bglucan fortified dahi (Bhaskar et al 2017) etc.…”
Section: Introductionmentioning
confidence: 99%
“…This indicated that the yogurt produced by Compounds E had the ability to withstand mechanical handling during dairy processing and transport. The thixotropic properties of fresh yogurt have been well established in previous studies (Sakin-Yilmazer et al, 2014;Xu et al, 2018). These could be quantified by the yogurt's ability to regain its initial structure when allowed to rest for a certain period after disturbing.…”
Section: Rheological Properties Of the Fermented Yogurtmentioning
confidence: 66%
“…First, we set the parameter to 50% of the compression deformation. The initial force was 0.02 N. Lastly, characteristics like chewiness, gumminess, cohesiveness, hardness, and springiness were measured, with a total of 5 measurements per sample [ 37 ].…”
Section: Methodsmentioning
confidence: 99%